Long-Term Efficacy of Maintenance Therapy for Multiple Myeloma: A Quantitative Synthesis of 22 Randomized Controlled Trials - Li, Jie-Li; Fan, Guang-Yu; Liu, Yu-Jie; Zeng, Zi-Hang; Huang, Jing-Juan; Yang, Zong-Ming; Meng, Xiang-Yu (Frontiers in Pharmacology, 2018)
Abstract We aimed to quantitatively synthesize data from randomized controlled trials (RCTs) concerning maintenance for multiple myeloma (MM). We searched electronic literature databases and conference proceedings to identify relevant RCTs. We selected eligible RCTs using predefined selection criteria. We conducted meta-analysis comparing maintenance containing new agents and conventional maintenance, and subgroup analysis by transplantation status and mainstay agent as well. We performed trial sequential analysis (TSA) to determine adequacy of sample size for overall and subgroup meta-analyses. We performed network meta-analysis (NMA) to compare and rank included regimens. A total of 22 RCTs involving 9,968 MM patients and 15 regimens were included, the overall quality of which was adequate. Significant heterogeneity was detected for progression-free survival (PFS) but not overall survival (OS). Meta-analyses showed that maintenance containing new agents significantly improved PFS but not OS (PFS: Hazard Ratio (HR) = 0.59, 95% Confidence Interval (CI) = 0.54 to 0.64; OS: HR = 0.93, 95% CI = 0.87 to 1.00), compared with controls. Subgroup analyses revealed lenalidomide-based therapies better than thalidomide-based ones (HR = 0.50 and 0.66, respectively; P = 0.001). NMA revealed that most of the maintenance regimens containing new agents were significantly better than simple observation in terms of PFS but not OS. Lenalidomide single agent was the most effective, considering PFS and OS both. We concluded that conventional maintenance has very limited effect. Maintenance containing new agents is highly effective in improving PFS, but has very limited effect on OS. Maintenance with lenalidomide may have the largest survival benefits. Emerging strategies may further change the landscape of maintenance of MM.